Forage Accumulation and Nutritional Characteristics of Brachiaria Cultivars Grown in a Semi-arid Environment - J. G. Rodrigues; G. dos S. Difante; L. C. V. Ítavo; M. de G. Pereira; A. L. C. Gurgel; A. B. G. da Costa; E. L. de L. Veras; G. O. de A. Monteiro; A. M. Dias; C. C. B. F. Ítavo (Tropical Animal Science Journal, 2023)
The evaluation of the nutritional value and parameters of ruminal fermentation of tropical forages is important, aiming at its efficient use in ruminant feeding. This study was developed to evaluate the forage accumulation, chemical composition, protodioscin content, digestibility, and in vitro degradation kinetics of different Brachiaria spp. cultivars in different evaluation periods. The research was carried out in the semi-arid region of Brazil, from April 2016 to April 2017. The experiment was laid out as a split-plot arrangement in a randomized block design in which five cultivars (B. decumbens cv. Basilisk, and B. brizantha cvs. Marandu, Paiaguás, Piatã, and Xaraés) represented the plot and four evaluation periods (establishment, transition, dry, and rainy) the subplot. There was a cultivar × period interaction effect for forage accumulation rate (FAR), for which cv. Xaraés showed the highest mean (54.1 kg/ha.day DM) in the rainy season. The lowest yield was found in cv. Paiaguás in the dry season (24.1 kg/ha.day DM). Cultivars Basilisk, Marandu, and Paiaguás had the highest crude protein content. The highest in vitro dry matter digestibility values were found in cv. Basilisk in the dry, transition, and rainy periods; cv. Marandu in the transition period, and cvs. Paiaguás and Piatã in their establishment. A correlation was found between the parameters of in vitro degradation kinetics and chemical composition. The protodioscin content was highest in cv. Basilisk, during its establishment (5.5 g/kg DM). Cultivars Paiaguás, Piatã, and Xaraés showed low protodioscin values (<1.0 g/kg DM). Cultivars Basilisk, Marandu, Paiaguás, Piatã, and Xaraés can be used as forage options in the semi-arid environment, as their forage accumulation potential and nutritional value are suitable for animal production even in periods of lower water availability.